2017
DOI: 10.1016/j.nmni.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Francisella tularensis in febrile patients seeking treatment at remote hospitals, northeastern Kenya, 2014–2015

Abstract: Tularaemia is a highly contagious infectious zoonosis caused by the bacterial agent Francisella tularensis. The aim of this study was to investigate the presence of antibodies to F. tularensis in febrile patients in northeastern Kenya. During 2014–2015, 730 patients were screened for anti-F. tularensis antibodies using a combination of ELISA and Western blot. Twenty-seven (3.7%) individuals were positive for F. tularensis. Tularaemia was not suspected by the treating clinicians in any of them. Our results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…As indicated before, the risk of false-positive results due to antigenic cross-reactions increases when considering low antibody titers (Syrjälä et al, 1986). In some studies, authors confirmed positive serological tests using Western blot to reduce false-positive results caused by antigenic cross-reactions (Jenzora et al, 2008;Splettstoesser et al, 2009;Zaḱutnáet al, 2015;Njeru et al, 2017). Besides, in many instances, the Western blot did not confirm positive ELISA tests, especially when ELISA titers were just above the cutoffs (Schmitt et al, 2005;Rossow et al, 2015).…”
Section: Seroepidemiological Studies On Tularemiamentioning
confidence: 95%
See 4 more Smart Citations
“…As indicated before, the risk of false-positive results due to antigenic cross-reactions increases when considering low antibody titers (Syrjälä et al, 1986). In some studies, authors confirmed positive serological tests using Western blot to reduce false-positive results caused by antigenic cross-reactions (Jenzora et al, 2008;Splettstoesser et al, 2009;Zaḱutnáet al, 2015;Njeru et al, 2017). Besides, in many instances, the Western blot did not confirm positive ELISA tests, especially when ELISA titers were just above the cutoffs (Schmitt et al, 2005;Rossow et al, 2015).…”
Section: Seroepidemiological Studies On Tularemiamentioning
confidence: 95%
“…The immunoblotting technique has been proposed as a confirmatory test in patients with positive MAT, IFA, or ELISA tests. The ladder-like band pattern obtained with F. tularensis LPS is considered as typical for this species (Porsch-Ozcürümez et al, 2004;Schmitt et al, 2005;Jenzora et al, 2008;Chaignat et al, 2014;Rossow et al, 2015;Zaḱutnáet al, 2015;Njeru et al, 2017). However, in many studies, western blot could not confirm a large number of positive tests obtained with other methods (Porsch-Ozcürümez et al, 2004;Schmitt et al, 2005;Rossow et al, 2015;Zaḱutnáet al, 2015;Njeru et al, 2017).…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations